Fatores psicossociais ao controle eficaz do regime terapêutico (adesão ao tratamento) em pessoas idosas hipertensas - Amaral, Jonábia Alves Demetrio (2021)
The human aging process is reflected in the demographic increase of people over 60 years old. As Systemic Arterial Hypertension (SAH) is one of the main diseases in this population, there is a need to understand the health/disease process in a psychosocial dimension. The general objective was to analyze the psychosocial factors involved in the Effective Control of the Therapeutic Regime related in elderly people with SAH. The research was carried out in two stages: 1) Social determinants as modifiable factors for adherence to hypertension treatment among elderly people; 2) Perception of hypertensive elderly people in relation to the effective control of the therapeutic regimen (adherence to treatment) in times of Covid's 19 pandemic. descriptive and exploratory, cross-sectional study. Data collection for the integrative review took place from June to December 2020, while data collection for the descriptive study took place from March to May 2021 and guaranteed the ethical issues recommended by Resolution CNS 510/16/ CNS /MS under protocol No. CAAE: 35501720.2.0000.5187. Regarding the social determinants of health, it was noticed that they are in the daily life of the elderly individual and that many of these, when not worked with the aging population, can be neglected and negatively interfere in the adherence to the treatment of SAH. The results of the first article showed that adherence to treatment requires the interaction of health professionals with elderly individuals, family members, social groups and society in general in order to benefit from guidance and health promotion. Regarding the perception that the participants reported regarding the effective control of the therapeutic regimen (adherence to the treatment), it was found that all individuals who try to control their blood pressure, had good conditions related to social determinants of health and that the pandemic of Covid 19 changed the healthy aging routine of the elderly in relation to physical activity, proper diet, social inclusion. It is concluded that the effective control of antihypertensive treatment occurs when the patient understands their health-disease process and it was observed that the coexistence groups are a valuable support network for the elderly person.